Research on vibration reduction test and frame modal analysis of rice transplanter based on vibration evaluation - Jin, Xin; Cheng, Qun; Tang, Qing; Wu, Jun; Jiang, Lan; Wu, Chongyou; Wang, Huankun (International Journal of Agricultural and Biological Engineering, 2022)
The chassis of rice transplanter tends to vibrate severely in the severe working environment, causing a severe effect on the operational performance and driving comfort. In order to avoid this situation, this paper constructs a vibration evaluation system of the rice transplanter and carries out experimental analysis. According to the optimal acceleration sensor placement scheme, a test platform system was designed. Taking the high-speed transplanter chassis as the research object, this study carried out the experiments modal analysis and optimization on the chassis. The three-dimensional model of the transplanting machine chassis established by SolidWorks was imported into ANSYS Workbench for finite element modal simulation analysis. Comparing the two modal analyses, it is found that the results data of the two analysis methods were very close. After optimization, the length x1, the section width x2 and the thickness of the hollow beam x3 of the main load-bearing beam of the frame were as follows : x1=1641.5 mm, x2 =26.7 mm, x3=5 mm, respectively. The maximum overshoot of the low-level system was reduced by 28.57%. It has been verified that the vibration of the whole machine has been effectively reduced. Keywords: chassis, high-speed rice transplanter, vibration evaluation, modal analysis DOI: 10.25165/j.ijabe.20221504.7244 Citation: Jin X, Cheng Q, Tang Q, Wu J, Jiang L, Wu C Y, et al. Research on vibration reduction test and frame modal analysis of rice transplanter based on vibration evaluation. Int J Agric & Biol Eng, 2022; 15(4): 116–122.